Draft Sixth Five Year Plan 1978-83 Sector Forestry - Planning Commission (Planning Commission, 1978)
The planning strategy in the Forestry sector is to achieve the primary object of maintaining the forests and Protecting the Sybil from erosion by replenishing the worked over forest and improving the growing stock of commercially valuable timber species which in turn will maintain the ecological and environmental balance. This operation will be carried out by harvesting .of the forest wealth at optimum level in perpetuity on a scientific basis following the sound, principle of forest management be ensure maintenance of ecological and environmental balance and conservation including protection of wild life in the islands.
Andaman and Nicobar Administration
Keywords: Forestry Sector of Andaman and Nicobar Islands; Artificial and Natural Regeneration of forest for Industrial Commercial Uses; Forestry Research; Survey and Demarcation and Settlement of forest; Wildlife and Environment Conservation; Development of Ninor Forest Produce; Intensification of Management; Communication and Now Conduction; Construction of buildings; Farm Forestry; Cooperation Sector; Village & Small Scale Industries